Potencialidades nutricionais e funcionais de quatro espécies frutíferas da biodiversidade da Região Nordeste. - Mendes, Ana Erbênia Pereira (2018)
Brazil is one of the most privileged countries in biodiversity worldwide. With distinct ecosystems distributed in its different regions, the country embraces a large number of native species, including in the Northeast region, still not exploited. This work was aimed at evaluating the composition and nutritional and functional potential of the fourth fruits of the biodiversity of the Northeast region of Brazil, including the araçá (Psidium sobralianum Landrum & Proença), bacuri (Platonia insignis Mart.), cajuí (Anacardium spp.) and mangaba (Hancornia speciosa Gomes). Each studied fruit has been analysed three lots from different localities of the Northeast region, trials of determining physico-chemical characteristics, macro and micronutrients content, determination of bioactive compounds and fractions of polyphenols, as well as evaluation of the antioxidant activity. Additionally, in araçá was evaluated in protection against ethanol-induced gastric lesion. The studied fruits presented acid character and significant nutrient content, in which the araçá was the fruit that was most contributed to the adequacy of iron intake (11% of the DRIs). The bacuri was highlighted by the largest quantity of lipids (2.68% ± 0.05), with greater predominance of oleic acid (4.28 mg/g). In general the fruits in study present low content of anthocyanins, yellow flavonoids and carotenoids. However the cajuí proved to be an excellent source of vitamin C for feeding (132. 27MG/100 g). Sixteen (16) fractions of phenolic compounds of the different fruits were identified and quantified and the araçá was the fruit that presented the highest phenolic content of the flavonoids group, in particular isoquercitrin (38.34 μg/g), myricetin (18.31 μg/g) and quercetin (13.40 μg/g). Furthermore, this fruit presented high phenolic total content (1123.33mg EAG/100g) and high antioxidant capacity in vitro (43.36 µ m Trolox/g). Gastric lesions were significantly improved with oral administration of araçá for promoting significant increase in glutathione levels (91.62 ± 65.54 Μ g/g of tissue) and decrease of malondialdeído (5168.33 ± 2676.39 nmol/mg of tissue) in the gastric mucosa. Knowledge of the potential of these underutilized species allows access to new markets with differentiated products from the nutritional and functional point of view in the food industry, pharmaceutical and nutraceutical, in which it stands out the araçá that demonstrated expressive activity in vitro and in vivo antioxidant.